Enhancing Innovative Work Behavior Through Innovation Climate: the Role of Cultural Intelligence and Green Transformational Leadership in Private Universities in Medan - Martin Martin; Darwin Lie; Robert Tua Siregar (Proceeding of The International Conference on Economics and Business, 2024)
This study looks at how cultural intelligence (CQ) and green transformational leadership (GTL) influence employees' innovative behavior (EIB), with innovation climate (IC) playing a role in between, at private universities in Medan City. This study uses a quantitative approach with an explanatory survey method. We conducted data analysis using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through Smart PLS software. The results showed that GTL had a significant positive effect on IC and EIB. IC was also shown to have a forceful and significant effect on EIB. Conversely, CQ showed a significant negative effect on IC and EIB, indicating that cultural diversity that is not managed effectively can hinder innovation. Mediation analysis indicated that IC significantly mediates the effect of GTL and CQ on EIB. However, the way CQ affects EIB through IC is still negative, meaning that if the innovation climate isn't supportive, CQ can actually have a harmful effect. These findings emphasize the importance of environmentally oriented transformational leadership and innovative climate in encouraging employee innovative behavior. Theoretically, this study integrates individual, leadership, and organizational dimensions in understanding innovative behavior. Practically, these findings provide implications for the development of HR management strategies in culturally diverse higher education environments.